The case of Evgenii Sergeevich Lyapin - Hollings, C (Institute of Mathematics and its Applications, 2012)
One of the major issues facing mathematics at present is the demand for immediate applications. Another (historical) example of such a policy may be found in Soviet ideological interference in mathematics, of which I will give a short description, before illustrating it with an account of an ideological attack on the Russian algebraist E. S. Lyapin.